Quasar Remote Access Trojan feature extraction depending on Ethical Hacking - Ibrahim, Mohanad R.; Thanoon, Karam (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
These days, computer Trojans had become in the top of the most dangerous types of malwares threats. There is a lot of remote access tools that have ability to manage and apply many features remotely. Quasar Trojan is one of the most uses for Remote Access Trojan (RAT). The researchers apply Quasar on real environment in lab (ethically and for education purposes) and this paper presents the capabilities of Trojans. This paper will present some of Quasar features by extract most important features also presents how to access remotely by using no-IP address (DUC) with other tools of applying access of internal network ethically.